Authic: computational tool for children with autistic spectrum disorder - Herrero, Concepción Pérez de Celis; García, María J. Somodevilla; Muñoz, Carmen Lara; Torres, Ivo H. Pineda; Aguilar, Tayde A. Castillo; Aguilar, Karina F. de Alba; Romero, Erick Romero (Revista Hipótese, 2017)
The AUTHIC as an assistive technology aims to develop tools which aid children with autism spectrum disorder (ASD) to understand and interpret facial expressions associated with an emotion, through interactive games supervised by a therapist. Since research is translational, health sciences findings in understanding emotion and the universality of facial expression support the multimedia applications development designed by user-centered methodologies and gamification. Learning routines enable training of ASD children to identify emotions in an interactive and entertaining way.